Optimization of hollow fiber-supported liquid membrane operating parameters for levulinic acid separation: Modeling and experimental investigation - Rajendaren, Vikneswary; Syed Mohd Saufi, Tuan Chik; Mior Ahmad Khushairi, Mohd Zahari (Elsevier, 2024)
Hollow fiber-supported liquid membrane (HFSLM) is a highly promising technology for the separation of levulinic acid (LA), which is one of the leading biomass products. This process is particularly advantageous for industrial-scale applications due to its capability for continuous extraction and back extraction within a single operational device. This study employed HFSLM for the extraction of LA from an aqueous solution. To optimize HFSLM performance, response surface methodology with central composite face-centered (CCF) design was used to fine-tune three key factors: the concentration of trioctylamine (TOA) as a carrier, the concentration of sodium hydroxide (NaOH) as a stripping agent, and the concentration of LA in the feed solution. The ideal operating conditions for HFSLM were determined to be 0.32 M TOA, 0.77 M NaOH, and 10.08 g/L LA, resulting in the highest LA extraction efficiency of 74.82 % ± 3.83 %. The study also investigated the mass transfer mechanisms within the HFSLM system. Key parameters such as the extraction equilibrium constant (Kex), stripping equilibrium constant (Kst), distribution ratio (D), aqueous mass transfer coefficient (kf), and membrane mass transfer coefficient (km) were determined. The km value, measured at 5.1012 × 10−3 cm/s, exceeded the kf value of 0.6613 × 10−3 cm/s, indicating that the rate-limiting step in LA transport occurred during its diffusion through the film layer separating the feed and organic phases. A new mathematical diffusion flux model focusing on the extraction side of the liquid membrane system was developed to estimate the concentration of LA at different times. The model offers valuable insights into the transport mechanisms during LA extraction using HFSLM and can serve as a benchmark for integrating HFSLM into actual biomass processing.